2014
DOI: 10.1016/j.metabol.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Association between circulating irisin levels and the promotion of insulin resistance during the weight maintenance period after a dietary weight-lowering program in obese patients

Abstract: Objective. Weight regain is associated with the promotion of insulin resistance. The newly discovered myokine irisin, which was proposed to be involved in the management of insulin sensitivity, could play a role in this process. This study aimed to investigate the association between irisin and reduced insulin sensitivity induced by weight regain.Materials/Methods. Insulin sensitivity was evaluated according to the homeostasis model assessment of insulin resistance (HOMA-IR) in 136 obese patients who followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
118
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(127 citation statements)
references
References 63 publications
8
118
1
Order By: Relevance
“…Studies have reported that irisin is related to BMI; however, irisin was not significantly correlated with BMI in other studies [23,24]. The circulating irisin levels have been shown to be negatively correlated with BMI [25][26][27], whereas some reports suggested that irisin concentrations were positively associated with BMI [20,28]. Moreover, although a few studies have demonstrated that there is no direct relationship between irisin and BMI, their results support the hypothesis of a positive correlation between irisin and BMI.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Studies have reported that irisin is related to BMI; however, irisin was not significantly correlated with BMI in other studies [23,24]. The circulating irisin levels have been shown to be negatively correlated with BMI [25][26][27], whereas some reports suggested that irisin concentrations were positively associated with BMI [20,28]. Moreover, although a few studies have demonstrated that there is no direct relationship between irisin and BMI, their results support the hypothesis of a positive correlation between irisin and BMI.…”
Section: Discussionmentioning
confidence: 86%
“…There is a possibility that irisin may be a surrogate marker for MetS. Most studies in adults showed that levels of irisin were linked to the incidence of T2DM [7], insulin resistance [19,20], and dyslipidemia [21], which are components of MetS. However, there were discrepancies reporting the relationship between irisin and metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…found that individuals who regain weight after initial weight loss had increased irisin levels corresponding with increased bodyweight, fat mass, fasting glucose, insulin, and HOMA‐IR compared to those maintaining a normal weight (Crujeiras et al. 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Plasma concentrations of insulin (Mercodia, Uppsala, Sweden) were measured using specific enzyme‐linked immunosorbent assays and assessed by means of an automated analyzer system (Triturus, Grifols, Barcelona, Spain). Insulin resistance was estimated by the homeostatic model assessment‐insulin resistance (HOMA‐IR) index according to the following formula: (fasting insulin (mU/L) × plasma glucose (mmol/L)/22.5) as previously reported (Crujeiras et al., 2014). Triglyceride‐glucose (TyG) index was calculated as: (ln [fasting triglycerides (mg/dl) × fasting plasma glucose (mg/dl)/2]) as described elsewhere (Navarro‐González, Sánchez‐Íñigo, Pastrana‐Delgado, Fernández‐Montero, & Martinez, 2016).…”
Section: Methodsmentioning
confidence: 99%